ChemInform Abstract: Semiconducting [(Bi4Te4Br2) (Al2Cl6‐xBrx)]Cl2 and [Bi2Se2Br](AlCl4): Cationic Chalcogenide Frameworks from Lewis Acidic Ionic Liquids. Issue 29 (1st July 2013) - Biswas, Kanishka; Chung, In; Song, Jung‐Hwan; Malliakas, Christos D.; Freeman, Arthur J.; Kanatzidis, Mercouri G.
Abstract: The new semiconducting halide‐chalcogenide [(Bi4 Te4 Br2 ) (Al2 Cl5.46 Br0.54 )]Cl2 (I) is synthesized by reacting Bi, Te, and excess AlCl3 in [emim]Br (closed glass vial, 165 °C, 5 d; 74% yield).